Optical, Electrical and Photoresponse Properties of Si-based Diodes with NiO-doped TiO2 Film Prepared by Sol-gel Method - Tataroglu, A.; Al-Sehemi, Abdullah G.; Ilhan, M.; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Springer, 2018)
The Ti1-xO2NixO films (x = 0.0, 0.05, 0.10 and 0.15) with various NiO contents were prepared by sol-gel technique. The prepared films were coated on n-Si substrate by spin coating technique. The optical and photoresponse properties of the fabricated Al/n-Si/Ti1-xO2NixO/Al diodes were investigated. The optical properties of the films were studied by transmittance and absorbance spectra. The photoconducting behavior of the diodes was investigated under various solar light intensities. The photocurrent of the diodes under illumination was higher than the dark current. This result confirms that the diodes exhibit both photoconducting and photodiode behavior. The photoresponsivity of the diodes are changed with NiO content.
Keywords: NiO doped TiO2 films; Diode; Optical and photoresponse properties; Photoconducting